The Synergistic Effect of Urban Canyon Geometries and Greenery on Outdoor Thermal Comfort in Humid Subtropical Climates - Peng, Mingxi; Huang, Haijing (Frontiers in Environmental Science, 2022)
Understanding the synergistic effect of multiple parameters is helpful for urban planners to designing sustainable cities in a holistic approach. The objective of this research is to investigate how the street aspect ratio, orientation and greenery parameters such as leaf area density(LAD) and aspect ratio of trees(ART) affect the microclimate and outdoor thermal comfort of street canyons in central business district under the local climate of Chongqing city. To achieve this goal, a series of single-parameters and multi-parameters simulation which followed an orthogonal design of experiments(ODOE) were conducted. The physiological Equivalent Temperature(PET) was adopted to assess the result of microclimate simulations for different urban models. The main findings are as follows: a) the street aspect ratio, orientation and ART of urban canyons play significant roles in affecting the microclimate variables at pedestrian level; b) there is an inverse relationship between the street aspect ratio and Tmrt, the same phenomenon can be found in the results of ART, and the deep canyons or canyons with dense trees experience the highest wind velocity, which develop “the effect of narrow” consequently; c) the E-W streets and shallow canyons suffer the warmest thermal conditions and longest extreme discomfort durations; d) the results of PET and meteorological parameters exhibits less significant variations between different values of LAD than those observed in the other three parameters